2013
DOI: 10.1039/c2gc36714a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic co-processing of Red Mud waste from the Bayer process and a crude untreated waste stream from bio-diesel production

Abstract: The production of the aluminum metal from bauxite ore and bio-diesel from triglyceride oils both generate large waste streams, and their management and valuation is therefore of great interest in Brazil and any other country with established or developing bio-fuel and aluminum industries. The integration of these two waste streams into the development of alternative technologies that utilize wastes as low-cost materials could potentially contribute to economic development as well as chemical sustainability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Table 3 lists the temperatures of the TPR peak (TTP) for all of the samples. Ordonez et al [36] and Schlaf et al [37] reported that the typical TPR [37]. HRM (400) showed a shoulder peak at 500℃ in addition to two reduction peaks.…”
Section: Characterization Of Rm and Hrmmentioning
confidence: 96%
“…Table 3 lists the temperatures of the TPR peak (TTP) for all of the samples. Ordonez et al [36] and Schlaf et al [37] reported that the typical TPR [37]. HRM (400) showed a shoulder peak at 500℃ in addition to two reduction peaks.…”
Section: Characterization Of Rm and Hrmmentioning
confidence: 96%
“…Work has been carried out on the use of Bayer residue as a construction additive or filling material (Deelwal et al, 2014). Limited work has been carried out on the use of Bayer residue as a coagulant or as an industrial catalyst, showing it may have potential in this area (Wang, et al, 2008b), for example to purify a bio-diesel waste stream (Resende et al, 2013). Work has also been carried out on iron recovery from Bayer residue (Liu and Naidu, 2014).…”
Section: Current Usesmentioning
confidence: 99%
“…1,10,18 Any alternative use of Red Mud as a catalyst could contribute to the reduction of environmental impact and at the same time add value to this material. 1,9,19 Desulfurization Sulfur, in both, its volatile SO x oxide or reduced H 2 S forms, constitutes a considerable environmental and technical problem. The sulfur compounds are highly undesirable in rening processes as they can lead to the deactivation of some catalysts used in crude oil processing and cause corrosion problems in pipelines, pumping and rening equipments, resulting in substantial nancial losses to the industry.…”
Section: Red Mudmentioning
confidence: 99%